The Effect of Product Quality and Halal Label MUI on Purchase Interest in Ms. Glow Skincare (Case Study of Ms. Glow Consumers in Kedungharjo, Widang, Tuban) - Siti Nur Anifah; Syuhada Syuhada; Ahmad Munir Hamid (AJER: Advanced Journal of Education and Religion, 2025)
Product quality and halal labels are factors that can influence consumer buying interest and are often used by consumers as a basis for considering whether or not they are interested in a product and deciding to make a purchase. The aim of this research is to analyze and find out how much influence: (1) product quality has on interest in buying Ms Glow skincare products in Kedungharjo, Widang, Tuban, (2) the halal label has on interest in buying Ms Glow skincare products in Kedungharjo Village, Widang District Tuban Regency (3) product quality and halal labels simultaneously affect interest in purchasing Ms Glow skincare products in Kedungharjo, Widang, Tuban. This type of research is quantitative research. The author's data collection method uses a questionnaire data collection model via Google Form. The population in this study were Ms Glow skincare customers in Kedungharjo, Widang, Tuban who purchased Ms Glow skincare products. The number of samples taken was 30 respondents using a saturated sample where all populations were sampled. The data analysis technique used is multiple linear regression analysis. The results of this research show that product quality (X1) has a significant influence on consumer buying interest in Ms Glow. This is proven by the calculated t value for the product quality variable which is 2.077 and the t table has a value of 2.056 which shows that t calculated > t table. Meanwhile, the significance value is 0.047 <0.05, so the product quality variable has a significant positive effect on consumers' buying interest in Ms Glow skincare. Meanwhile, the Halal Label (X2) is t calculated at 5.734 and the t table value is 2.056 which shows that t calculated > t table. Meanwhile, the significance value is 0.000 <0.05, so the halal label variable has a significant effect on consumers' buying interest in Ms Glow skincare. Based on the results of the F test (39.688 > 2.96), which means that the product quality and halal label variables, if tested together or simultaneously, have a significant effect on the purchase interest variable. Based on the results of the R Square value of 0.727 or 72.7%, this figure shows the large influence of product quality variables and halal labels on the combined purchase interest variable, while the remaining 27.3% is influenced by other variable factors outside this research.